Women’s opinion in the light of possibility of lengthening the retirement age in Poland - Thel, Karolina (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Demographic changes seen in Europe represent the challenge for social protection system and for the job market. The increasing number of pensioners results not only from ageing population, but also from the privileges for pensioners existing in our country. A proposal to lengthen the retirement age of citizens seems to be right in the light of forecasts concerning the pace of the society ageing process and its consequences for the labour market, pension system and the social protection, but majority of polish society is against (around 80%). Because of lower salaries, breaks in job activity caused by family responsibilities and shorter period of job activity, women are group of risk of poverty in old age. In my research I deal with possibilities to lengthen women' activity on the labour market concerning following factors: individual history of professional activity, family status, education, competence, work-life balance. My own research model includes deepened interviews with 50-65 years old women, who share the experience of being a mother of a grown up daugther.